A technique to treat Descemet’s membrane detachment following cataract surgery - Liu, Wenjie; Ma, Jack X.; Tan, Xin; Chai, Feiyan; Liu, Jiewei (Frontiers in Medicine, 2024)
We describe a technique to reattach Descemet's membrane detachment following cataract surgery. From the main clear corneal cataract incision, aqueous humor is ejected completely by apposition of the cornea to the iris for approximately 3 seconds. This ensures the fluid in the space between the stroma and Descemet's membrane is ejected and the detached Descemet's membrane returns to its original position. Through a paracentesis 180 degrees away from the Descemet's membrane detachment, sterile air is injected to maintain a complete air-filled chamber. Full air tamponade is maintained for 20 minutes and then approximately one third of the air is ejected from the chamber to prevent increase of intraocular pressure postoperatively.